2018
DOI: 10.3390/molecules23020445
|View full text |Cite
|
Sign up to set email alerts
|

Food-Grade Encapsulation Systems for (−)-Epigallocatechin Gallate

Abstract: (−)-Epigallocatechin gallate (EGCG) has attracted significant research interest due to its health-promoting effects such as antioxidation, anti-inflammation and anti-cancer activities. However, its instability and poor bioavailability have largely limited its efficacy and application. Food-grade materials such as proteins, carbohydrates and lipids show biodegradability, biocompatibility and biofunctionality properties. Food-grade encapsulation systems are usually used to improve the bioavailability of EGCG. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 95 publications
(138 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, chronic inflammation shows adverse effects for the bone healing 40) . Meanwhile, it is consensual that EGCG is a strong antioxidant and anti-inflammatory agent 8) . Additionally, the presence of EGCG in biomaterials treated by coating or modification approaches alters the materials properties, including wettability, charge, and calcium deposition 18,22) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, chronic inflammation shows adverse effects for the bone healing 40) . Meanwhile, it is consensual that EGCG is a strong antioxidant and anti-inflammatory agent 8) . Additionally, the presence of EGCG in biomaterials treated by coating or modification approaches alters the materials properties, including wettability, charge, and calcium deposition 18,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG), the most abundant bioactive polyphenolic compound in green tea, is a known health-promoting ingredient with antioxidant, antibacterial, anti-inflammatory, and anti-cancer properties 8) . The molecule potentially has wide-ranging pharmacological effects on cardiac 9) , inflammatory 10) , oncological 11) , and psychiatric diseases 12) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is convincing evidence that this compound has a stronger antioxidant potential than other green tea catechins, and that it is even more effective in ROS scavenging than vitamins C and E (Rice-Evans et al, 1995). EGCG has been also repeatedly shown to exhibit anti-inflammatory, anti-atherogenic and anti-cancer activities (Singh et al, 2011;Shi et al, 2018). The data from epidemiological studies devoted to investigating EGCG are, however, controversial and often conflicting with in vitro findings.…”
Section: Nano-epigallocatechin-3-gallatementioning
confidence: 99%
“…In fact, numerous researches revealed that nanoencapsulation system has been one of the prominent nano delivery systems which significantly increases EGCG stability and improves drug release rate, which partially contributes to the increased cellular uptake of EGCG. In another research reported that the chitosanbased nanoparticulate systems have capable to enhance the EGCG bioavailability [87][88][89][90]. Dube et al, 2013, compared the intestinal absorption of free EGCG and nano-EGCG (CSNP) using excised mouse jejunum.…”
Section: Solid Lipid Nanoparticles (Sln)mentioning
confidence: 99%